1,25-dihydroxyvitamin-D3 distinctly impacts the paracrine and cell-to-cell contact interactions between hPDL-MSCs and CD4+ T lymphocytes - Behm, Christian; Miłek, Oliwia; Schwarz, Katharina; Rausch-Fan, Xiaohui; Moritz, Andreas; Andrukhov, Oleh (Frontiers in Immunology, 2024)
Introduction Human periodontal ligament-derived mesenchymal stromal cells (hPDL-MSCs) possess a strong ability to modulate the immune response, executed via cytokine-boosted paracrine and direct cell-to-cell contact mechanisms. This reciprocal interaction between immune cells and hPDL-MSCs is influenced by 1,25-dihydroxyvitamin-D3 (1,25(OH)2D3). In this study, the participation of different immunomodulatory mechanisms on the hPDL-MSCs-based effects of 1,25(OH)2D3 on CD4+ T lymphocytes will be elucidated using different co-culture models with various cytokine milieus. Material and methods hPDL-MSCs and CD4+ T lymphocytes were co-cultured indirectly and directly with inserts (paracrine interaction only) or directly without inserts (paracrine and direct cell-to-cell contact interaction). They were stimulated with TNF-α or IL-1β in the absence/presence of 1,25(OH)2D3. After five days of co-cultivation, the CD4+ T lymphocyte proliferation, viability, and cytokine secretion were analyzed. Additionally, the gene expression of soluble and membrane-bound immunomediators was determined in hPDL-MSCs. Results In the indirect and direct co-culture model with inserts, 1,25(OH)2D3 decreased CD4+ T lymphocyte proliferation and viability. The direct co-culture model without inserts caused the opposite effect. 1,25(OH)2D3 mainly decreased the CD4+ T lymphocyte-associated secretion of cytokines via hPDL-MSCs. The degree of these inhibitions varied between the different co-culture setups. 1,25(OH)2D3 predominantly decreased the expression of the soluble and membrane-bound immunomediators in hPDL-MSCs to a different extent, depending on the co-culture models. The degree of all these effects depended on the absence and presence of exogenous TNF-α and IL-1β. Conclusion These data assume that 1,25(OH)2D3 differently affects CD4+ T lymphocytes via the paracrine and direct cell-to-cell contact mechanisms of hPDL-MSCs, showing anti- or pro-inflammatory effects depending on the co-culture model type. The local cytokine microenvironment seems to be involved in fine-tuning these effects. Future studies should consider this double-edged observation by executing different co-culture models in parallel.